Three new records of Heteroptera in Slovenia - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2016)
Three species of Heteroptera are reported for Slovenia. Belonochilus numenius is an introduced Nearctic species. Phytocoris confusus was found in the vicinity of one of its syntype localities. Ochetostethus balcanicus is a north Mediterranean species found at the northern edge of its distribution.
Keywords: Heteroptera; new records; nove najdbe; Slovenia; Slovenija; stenice